The The Lifetime Cost and Services Length of Public Sector Employees in Pakistan - Khan, Muhammad Ajmal; Khan, Muhammad Jehangir; Khan , Nadeem Ahmad (Journal of Public Policy Practitioners, 2025)
This study estimates the discounted lifetime costs and lengths of service of public sector employees in Pakistan. The revised BPS pay scales of 2022 were used to assess three different scenarios. The lifetime cost is composed of lifetime salaries, commuted pensions, and monthly pensions. The findings indicate that, under the third scenario, the average lifetime cost for a BS 1-4 who retires in their 60s amounts to approximately 36.9 million rupees. For supporting staff (BPS 5-16), the discounted lifetime cost is 59.1 million rupees. Moreover, the average lifetime cost for employees in BPS 17-19 is 140.7 million rupees. Furthermore, the study also analyzed the average length of service for different employee categories. For BS 1-4 employees, the average length of service is 39 years, and the government bears their financial liability, on average, for 53 years. In the case of supporting staff, the average length of service is 32 years, and the government bears their financial liability for 47 years. Finally, for BPS-17-19 officers, the average length of service is 29 years, and the government bears their financial liability for 44 years. These findings can contribute to a better understanding of the financial implications associated with different employee categories and help inform policy decisions in the public sector.